Comparison of Türkiye and Singapore in the Context of PISA and TIMSS Performances - Dikmen, Melih; Yildirim, Ayfer (Marmara Üniversitesi, 2026)
International assessments such as PISA and TIMSS enable the comparative analysis of countries’ education systems and the measurement of student achievement through objective indicators. This study aims to compare the PISA and TIMSS performance of Türkiye and Singapore and to examine the pedagogical and structural factors underlying achievement differences. In addition, the study seeks to offer evidence-based recommendations for the improvement of the Turkish education system. The research was conducted using the document analysis method, one of the qualitative research designs. In this context, the horizontal approach of comparative education was adopted. Reports published by the OECD, IEA, the NCEE, and the Ministry of National Education (MoNE), as well as relevant theses and academic articles, were analyzed using content and descriptive analysis techniques. The findings reveal that Singapore has consistently demonstrated high achievement in mathematics, science, and reading, whereas Türkiye, despite recent improvements in TIMSS, still performs below the OECD average. It was determined that Singapore’s sustainable success is associated with teacher quality, inquiry-based learning, and practice-oriented instructional strategies. In the Turkish context, exam-oriented approaches, limited opportunities for hands-on learning, and inequalities in resource distribution were found to constrain educational development. In conclusion, differences in educational achievement can be said to be shaped by the interaction of pedagogical, structural, and cultural factors. For Türkiye to achieve sustainable improvement in international assessments, it is necessary to strengthen equality of opportunity in education and to expand the use of practice-based teaching methods.

PISA ve TIMSS gibi uluslararası değerlendirmeler, ülkelerin eğitim sistemlerinin karşılaştırmalı biçimde analiz edilmesine ve öğrenci başarılarının nesnel göstergelerle ölçülmesine olanak tanımaktadır. Bu çalışma, Türkiye ile Singapur’un PISA ve TIMSS performanslarını karşılaştırmayı ve başarı farklılıklarının ardındaki pedagojik ve yapısal etkenleri incelemeyi amaçlamaktadır. Ayrıca Türk eğitim sisteminin geliştirilmesine yönelik kanıta dayalı öneriler sunulması hedeflenmektedir. Araştırma, nitel araştırma desenlerinden doküman analizi yöntemiyle yürütülmüştür. Bu doğrultuda karşılaştırmalı eğitimin yatay yaklaşımı benimsenmiştir. OECD, IEA, NCEE ve Millî Eğitim Bakanlığı raporları ile ilgili tez ve akademik makaleler içerik ve betimsel analiz teknikleriyle değerlendirilmiştir. Bulgular, Singapur’un matematik, fen ve okuma alanlarında istikrarlı biçimde yüksek başarı gösterdiğini; Türkiye’nin ise TIMSS’te son yıllarda ilerleme kaydetmesine rağmen hâlen OECD ortalamasının altında performans sergilediğini ortaya koymaktadır. Singapur’un sürdürülebilir başarısının öğretmen niteliği, sorgulamaya dayalı öğrenme ve uygulama temelli öğretim stratejilerine dayandığı belirlenmiştir. Türkiye’de ise sınav merkezli yaklaşımların, sınırlı uygulamalı öğrenme fırsatlarının ve kaynak dağılımındaki eşitsizliklerin gelişimi sınırlandırdığı saptanmıştır. Sonuç olarak eğitimdeki başarı farklılıklarının pedagojik, yapısal ve kültürel etkenlerin etkileşimiyle şekillendiği söylenebilir. Türkiye’nin uluslararası değerlendirmelerde sürdürülebilir bir gelişme sağlayabilmesi için eğitimde fırsat eşitliğini güçlendirmesi ve uygulamaya dayalı öğretim yöntemlerini yaygınlaştırması gerekmektedir.
PISA ve TIMSS Performansları Bağlamında Türkiye ve Singapur’un Karşılaştırılması
Keywords: Cross-Cultural Comparisons of Education: International Examinations; Eğitimin Kültürler Arası Karşılaştırmaları:Uluslararası Sınavlar; Comparative and Cross-Cultural Education; Karşılaştırmalı ve Kültürlerarası Eğitim